CompTIA advanced security practitioner (CASP) CAS-002 cert guide - McMillan, Troy; Abernathy, Robin M. (Pearson IT Certification, 2015)
Trust the best selling Authorized Cert Guide series from Pearson IT Certification to help you learn, prepare, and practice for exam success. These guides are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. Master CompTIA® Advanced Security Practitioner (CASP) CAS-002 exam topics Assess your knowledge with chapter-opening quizzes Review key concepts with exam preparation tasks This is the eBook edition of the CompTIA® Advanced Security Practitioner (CASP) CAS-002 Authorized Cert Guide. This eBook does not include the companion CD-ROM with practice exam that comes with the print edition. CompTIA® Advanced Security Practitioner (CASP) CAS-002 Authorized Cert Guide presents you with an organized test preparation routine through the use of proven series elements and techniques. "Do I Know This Already?" quizzes open each chapter and enable you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. CompTIA® Advanced Security Practitioner (CASP) CAS-002 Authorized Cert Guide focuses specifically on the objectives for CompTIA's CASP CAS-002 exam. Expert security certification training experts Robin Abernathy and Troy McMillan share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. Well-regarded for its level of detail, assessment features, comprehensive design scenarios, and challenging review questions and exercises, this authorized study guide helps you master the concepts and techniques that will enable you to succeed on the exam the first time. The authorized study guide helps you master all the topics on the CompTIA CASP exam, including: Enterprise security: cryptography; storage; network/security components, concepts, and architectures; host controls; application vulnerabilities/controls Risk management and incident response: business influences/risks; risk mitigation; privacy policies / procedures; incident response/recovery Research, analysis, and assessment: industry trends; securing the enterprise; assessment tools / methods Integration of computing, communications, and business disciplines: business unit collabo...